Implementasi Continuous Integration dan Otomatisasi Monitoring Job Server Dengan Jenkins pada Compute Engine - Jek Siang, Jong; Harrius, Giovanni; Wibowo, Argo (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Job management, such as data migration for each division in a retail company, is still carried out separately on different servers. The damage reporting system is also still handled manually by the user. This results in difficulties in monitoring and handling damage to the job server. In this research, a system was implemented to automate monitoring, reporting, as well as unite separate jobs on several servers. The system created is based on Jenkins and integration with Python, Oracle Database, and PostgreSQL on a Google Compute Engine server. The resulting output is an email that is automatically created if an error occurs in running the job server, containing the log that is generated when the job server is running. System testing was carried out on 2 employees from each division according to their roles. The testing stages carried out are to ensure that the job performs according to its objectives, employees can carry out the job, and ensure that the damage job is sent successfully by email. Of all the tasks given, all employees successfully completed the tasks given. It can be concluded that the system has succeeded in meeting the needs of employees from each division, job server damage reports have been successfully standardized and sent automatically